Dampak Likuiditas, Leverage, dan Profitabilitas Mengenai Keputusan Hedging Perusahaan Perbankan di Bursa Efek Indonesia Periode 2019-2022 - Ustiananda, Firza Zafiral; Imronudin, I (SAFE-Network, 2025)
This study aims to analyze the effect of liquidity, leverage, and profitability on hedging decisions in banking sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2022. The data used are secondary data obtained from the company's annual financial reports published on the IDX. With the purposive sampling method, 52 data samples were obtained from 13 companies that met the research criteria. Data analysis was carried out using logistic regression to evaluate the relationship between the independent variables (liquidity, leverage, and profitability) and the dependent variable (hedging decisions). The results of the study indicate that liquidity has a positive and significant effect on hedging decisions, leverage has no significant effect, and profitability has a positive and significant effect. These findings emphasize the importance of liquidity and profitability in determining hedging policies, while leverage is not a significant factor in making these decisions. This study is expected to provide practical and theoretical contributions in the field of financial risk management and become a reference for companies to manage exchange rate risk through hedging strategies.